2009
DOI: 10.1111/j.1365-2966.2009.14694.x
|View full text |Cite
|
Sign up to set email alerts
|

On the tidal evolution of Hot Jupiters on inclined orbits

Abstract: Tidal friction is thought to be important in determining the long-term spin-orbit evolution of short-period extrasolar planetary systems. Using a simple model of the orbit-averaged effects of tidal friction, we study the evolution of close-in planets on inclined orbits, due to tides. We analyse the effects of the inclusion of stellar magnetic braking by performing a phase-plane analysis of a simplified system of equations, including the braking torque. The inclusion of magnetic braking is found to be important… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
304
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 228 publications
(317 citation statements)
references
References 54 publications
10
304
3
Order By: Relevance
“…Since younger stars are known to rotate more rapidly than those matured, gravity darkening is available to unveil the distribution of φ for the younger systems by the future observations. Although tidal evolution of φ causes the initial memory on the formation process of hot Jupiters to be lost (Barker & Ogilvie 2009, Lai 2012, Xue et al 2014, one can minimize this undesirable effect by preferentially selecting younger systems as targets to measure φ. These aspects suggest that gravity-darkening (combined with nodal precession, if possible) model is very useful to study the formation scenario of close-in planets.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since younger stars are known to rotate more rapidly than those matured, gravity darkening is available to unveil the distribution of φ for the younger systems by the future observations. Although tidal evolution of φ causes the initial memory on the formation process of hot Jupiters to be lost (Barker & Ogilvie 2009, Lai 2012, Xue et al 2014, one can minimize this undesirable effect by preferentially selecting younger systems as targets to measure φ. These aspects suggest that gravity-darkening (combined with nodal precession, if possible) model is very useful to study the formation scenario of close-in planets.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Tidal evolution of the system is computed by numerical integration of equations (19) - (21) in Correia et al (2011). The efficiency of tidal effect is also represented by the reduced tidal quality factor Q, which is written in terms of the above parameters as Q ≡ 3 4nk2∆t (Barker & Ogilvie 2009, Lai 2012, Rogers & Lin 2013, Xue et al 2014. We adopt our short solution as initial conditions and the values of Love number and tidal delay time estimated for Sun-like stars (k 2 = 0.028 and ∆t = 0.1 s following Correia et al 2011, which gives Q ∼ 10 6 for an orbital period of 0.448413 days).…”
Section: Long-term Dynamical Stabilitymentioning
confidence: 99%
“…where Q is the equivalent tidal dissipation factor in the star (defined as 3/2Q /k 2, * , where Q is the standard tidal dissipation factor and k 2,1 its Love number -see Barker & Ogilvie 2009). Using the parameters from Table 2 we obtain:…”
Section: Tidal Evolutionmentioning
confidence: 99%
“…Specifically, the inward migration timescale for a planet of mass M p in a circular orbit of period P around a star of mass M , radius R and spin period P is (Barker & Ogilvie 2009):…”
Section: Tidal Evolutionmentioning
confidence: 99%
“…The effect of the coupling between tides and magnetic braking on the evolution of short-period extrasolar planetary systems was studied by Barker & Ogilvie 2009. They found that neglecting magnetic braking in this type of systems results in a very different outcome of the evolution.…”
Section: Introductionmentioning
confidence: 99%